Socialisation of Blue Beach Tourism Activity Area Based on Bathymetry Contour in Tanjung Merdeka Village, Tamalate District, Makassar City - Rachman, Taufiqur; Juswan, Juswan; Alie, Muhammad Zubair Muis; Ashury, Ashury; Husain, Firman; Suyono, Suyono (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The tourist activities at Blue Beach are divided into 3 categories: swimming, water rides and fishing. The implementation of activities in the water poses a risk to tourists, which has the potential to cause accidents and even fatalities. This is due to the lack of segregation of areas for the implementation of the three beach tourism activities, which makes it difficult for tour managers to monitor tourists. For this reason, tour managers will be equipped with knowledge on the importance of dividing beach tourism activity areas based on bathymetric contours and the use of warning flags as safety signs for beach tourism activities. This socialisation can increase the awareness of tourism managers of potential hazards and disasters in the tourist sites they manage, by completing early warning signs of potential hazards of beach tourism activities. This socialisation is done in partnership with community-based tourism managers, namely Non-Governmental Organizations (NGO) of Tanjung Merdeka. The increase in knowledge and understanding of the socialisation material among the participants was 44.9 points. The service activity safety sign products were submitted by the service team in the form of a Blue Beach tourism activity map based on bathymetry contours and beach safety warning flags as occupational safety and health-based signs in the Blue Beach tourism area.